Enys men [videorecording (DVD)] - Jenkin, Mark; Woodvine, Mary; Rowe, Edward; Crowe, Flo; Woodvine, John, 1929- (Neon, 2023)
A wildlife volunteer on an uninhabited island descends into madness, pushing her into a living nightmare.